USING A PROBLEM SITUATION IN A COMPREHENSIVE TEST (BASED ON THE EXAMPLE OF PREPARATION FOR INTERCULTURAL BUSINESS INTERACTIONS WITHIN THE ASIAN PACIFIC RIM) - Albina G. Dolgan (National Research Mordova State University, 2016)
Introduction: nowadays Russian people are proactively seeking cooperation with the Asian Pacific Rim. Considering this the author has developed a curricular for institutions of higher learning training students in intercultural business interaction in this region within such disciplines as "Foreign language" and "Professional foreign language". Materials and Methods: the author puts forward a comprehensive test as a way to define the level of students' preparedness for business interaction within the Asian Pacific Rim, to test that they understand what they learn and to identify qualitative indicators attending to acquisition of content, and development of communicative and linguistic competences, as well as such necessary characteristics as pragmatism and tolerance. The comprehensive test elaboration was based on A. A. Verbitskiy and E. E. Kreslavskaya's method of assessing the students' understanding of meaning and significance of information. Results: drawing upon ideas of researchers studying intercultural communication, East Asian peoples' values, region's social, cultural and economic problems, the author proposes some special direction for the learning process - it should orient the Far Eastern students to take into consideration values, behaviours, mental and cultural specifics of partners from China, Korea, Japan and other neighboring countries in the business interaction. It is impossible to subdivide such interaction into professional and social spheres, so the author has chosen a problem situation to be a basic form for organising the learning process. The prob- lem situations of the social and professional character have been taken from East Asia business practices. Discussion and Conclusions: to solve the problem how to check students' understanding of the learning information, the author has developed a comprehensive test where a problem situation is also used. The paper's objective is to show how these problem situations written in English work within the comprehensive test. The author substantiates the choice of this method and provides factors which speak about its efficiency. The paper gives a detailed description of the problem situation working mechanism, contains examples of problem situations and options to solve them. The analysis of comprehensive test results demonstrated by non-linguistic higher school students' is also given a thorough account.